A One Health perspective on recreational fisheries - Steven J. Cooke; Andy J. Danylchuk; Joel Zhang; Vivian M. Nguyen; Len M. Hunt; Robert Arlinghaus; Kathryn J. Fiorella; Hing Man Chan; Tony L. Goldberg (Canadian Science Publishing, 2024)
Recreational fisheries involve an intimate connection between people, individual fish, and the environment. Recreational fishers and their health crucially depend on healthy fish and ecosystems. Similarly, fish and ecosystems can be impacted by the activities of people including recreational fishers. Thus, amplified by the global interest in recreational fishing, we posit that recreational fishing is particularly suited as an empirical system to explore a One Health perspective, with a goal of creating pathways to better manage such socio-ecological systems for the benefit of people, fish, and the environment. Although zoonoses are uncommon in fishes, fish can carry pathogens, biotoxins, or contaminants that are harmful to people. When captured and released, fish can experience stress and injuries that may promote pathogen development. Similarly, when humans contribute to environmental degradation, not only are fish impacted but so are the humans that depend on them for nutrition, livelihoods, culture, and well-being. Failure to embrace the One Health perspective for recreational fisheries has the potential to negatively impact the health of fish, fisheries, people, society, and the aquatic environment-especially important since these complex social-ecological systems are undergoing rapid change.